Impact of fine particulate matter (PM2.5) smoke during the 2019 / 2020 Australian bushfire disaster on emergency department patient presentations - Jamie Ranse; Matthew Luther; Attila Hertelendy; Richard Skinner (Elsevier, 2022)
Aim: The aim of this paper was to describe the patient characteristics and outcomes from a metropolitan emergency department (ED) during the 2019/2020 'Black Summer Bushfires' disaster in Australia and compare the patient characteristics and outcomes to a matched period from the same ED one year earlier. Background: Years of drought, low relative humidity, high temperatures, and high forest fuel loads led to catastrophic fire conditions across Australia during 2019 and 2020. As a result; 33 people died, 3 billion animals and 24 to 40 million hectares were lost, and 3,000 homes were destroyed. The impact of wildfire smoke is emerging in the literature regarding an exacerbation of respiratory, cardiac and cardiovascular disease. However, the impact on Australian EDs is minimally reported in the literature. Method: This retrospective cross-sectional cohort study used routinely collected data from the ED patient information system from one metropolitan Australian ED. Data were obtained for patient presentations during the 2019/2020 Black Summer Bushfire period and a matched period, 2018/2019, one year earlier. Daily mean air quality indicators (PM2.5, PM10) were obtained from the nearest air quality monitoring station. Data analysis included descriptive statistics, correlation coefficient and inferential statistics. Statistical significance was set at p ≤ 0.05. Results: The 2019/2020 study period had a statistically significantly higher airborne particulate matter (PM2.5) when compared to the matched period (p=<0.001), with comparable presentations between the study periods. However, an increase in respiratory related presentations (p<0.001; χ2 = 34.31) was noted in the 2019/2020 period, with a positive correlation between daily increasing mean air quality (PM2.5, PM10) and increasing patient presentations with respiratory related illness (p<0.001). Proportionately, patient demographics; mode of arrival, triage category, length of stay and admissions did not differ between periods. However, there was an increase in the raw number of patients being admitted to hospital with respiratory related illnesses, with a statistically significantly longer stay in the ED when compared to those discharged home (p<0.001). Conclusions: Wildfires produce smoke and subsequently poor air quality. The 2019/2020 Black Summer wildfire disaster in Australia resulted in an increase in respiratory-related patient presentations to the ED. Targeted public warning systems could be implemented in an attempt to limit an individual's exposure to wildfire smoke. Further, health services should monitor air quality as a predictor of patient presentations and subsequent health service demand, in support of ED preparedness.